The Histone Deacetylase Inhibitor I13 Induces Differentiation of M2, M3 and M5 Subtypes of Acute Myeloid Leukemia Cells and Leukemic Stem-Like Cells - Ma, Xiangyu; Zhao, Mengjie; Wu, Zhuo-Xun; Yao, Jingfang; Zhang, Lei; Wang, Jinhong; Hu, Zhenbo; Wei, Liuya; Chen, Zhe-Sheng (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is a heterogeneous hematologic malignancy characterized by reduced differentiation of myeloid cells and uncontrolled cell proliferation. AML is prone to drug resistance and has a high recurrence rate during treatment with cytarabine-based chemotherapy. Our study aims to explore the cell differentiation effect of a potent histone deacetylase inhibitor (HDACi), I13, and its possible mechanism on AML cell lines (Kasumi-1, KG-1, MOLM-13 and NB4). It has been shown that I13 can significantly inhibit proliferation and colony formation of these AML cells by inducing cell differentiation coupled with cell-cycle exit at G0/G1. Mechanically, I13 presented the property of HDAC inhibition, as assessed by the acetylation of histone H3, which led to the differentiation of AML cells. In addition, I13 activated the antigen-processing and presentation signaling pathways indicating that I13 maybe has the potential to promote immune cells to recognize leukemic cells and respond directly against leukemic cells. These results indicated that I13 could induce cell differentiation of M3 and M5 subtypes of AML cells, M2 subtype AML cells with t(8;21) translocation and leukemic stem-like cells. Therefore, I13 could be an alternative compound which is able to overcome differentiation blocks in AML.